Practical Teaching Methods as a Factor in Achieving the Effectiveness of Education - Rakhimov Zоkir Toshtemirovich (Zien Journals, 2022)
The reform of the education system, the main issues facing the modern education system, is that practical teaching methods are a factor in achieving educational efficiency, and pedagogues are required not only to know science thoroughly, but also to skillfully convey their knowledge to the minds of students, as well as for students to master science thoroughly. the important aspects of the used methods, the training of knowledgeable specialist personnel, the development of human potential depends on the teachers in all respects, their ability to organize and teach the educational process with knowledge, the organization of the educational process, the use of educational methods that help students gain in-depth knowledge, the organization of the educational process is the responsibility of the teacher It is interpreted that it requires not only deep knowledge, but also pedagogical skills, knowledge of various methods of teaching and continuous work on oneself, and the need for everyone to learn how to think
Keywords: student; education; teaching; process